Food Sovereignty Indicators for Indigenous Community Capacity Building and Health - Blue Bird Jernigan, Valarie; Maudrie, Tara L.; Nikolaus, Cassandra Jean; Benally, Tia; Johnson, Selisha; Teague, Travis; Mayes, Melena; Jacob, Tvli; Taniguchi, Tori (Frontiers in Sustainable Food Systems, 2021)
Food insecurity, defined as a lack of stable access to sufficient and nutritious food, is a global public health priority due to its relationships with diminished mental and physical human health. Indigenous communities experience disproportionality high rates of food insecurity as a byproduct of settler-colonial activities, which included forced relocation to rural reservation lands and degradation of traditional subsistence patterns. Many Indigenous communities have worked to revitalize their local food systems by pursuing food sovereignty, regularly expressed as the right and responsibility of people to have access to healthy and culturally appropriate foods, while defining their own food systems. Food sovereignty is a promising approach for improving health. However, limited literature is available that identifies the diverse practices of food sovereignty or strategies communities can implement to strengthen their food sovereignty efforts. This article reviews the scientific literature and highlights key indicators that may support community capacity building for food sovereignty and health. The seven indicators are: (1) access to resources, (2) production, (3) trade, (4) food consumption, (5) policy, (6) community involvement, and (7) culture. A total of 25 sub-indicators are outlined to allow communities to understand how an indicator is operationalized as well as explore their own community's progress within each indicator. It is not expected that every indicator and their subcategories will apply fully to any given Indigenous community, and the application of these indicators must be adapted for each community's local context, however the indicators may provide support for building and assessing efforts to create more sustainable Indigenous food systems.